Pengaruh Dompet Digital, Promosi Penjualan dan Kualitas Pelayanan terhadap Keputusan Pembelian Konsumen Indomaret (Studi Kasus pada Konsumen Indomaret di Jakarta Selatan) - Pusporini Pusporini; Lina Aryani; Anggi Angga Resti (Universitas Batanghari, 2023)
This research is a research using quantitative methods with the aim of knowing the effect of digital wallets, sales promotions, and service quality on Indomaret consumer purchasing decisions. The population in this study are Indomaret consumers in South Jakarta with a sample of 100 consumers who have transacted at Indomaret using a digital wallet. Sampling method Probability sampling with Purposive Sampling. This study used a questionnaire to collect data and SmartPLS 4.0 software for data processing tools. The results of this study indicate that (1) Digital Wallet has a positive and significant effect with a path coefficient value of 0.427. (2) Sales promotion has a positive and significant effect with a path coefficient value of 0.448. (3) Service Quality has an effect and is not significant with a path coefficient of 0.046 on purchasing decisions. The contribution of digital wallets, sales promotions and service quality together to purchasing decisions is 78.3%, of which the remaining 21.7% is explained by other variables.